Tourette Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1989)
The current concepts of Tourette syndrome, including research diagnostic criteria formulated by a workshop sponsored by the Tourette Syndrome Association, are reviewed from the Department of Neurology, University of Rochester School of Medicine, Rochester, NY.